Hemodynamic changes in hypertensive patients due to extubation - Bayar, M.; Bestas, A.; Yayla, T.; Erhan, O.L. (My University, 2000)
Purpose: In this study we investigated the changes in heart rate and blood pressure before and after extubation in hypertensive patients undergoing isoflurane, enflurane and propofol+fentanyl anaesthesia. Material and Methods: Sixty-six patients who were in the 2nd group of ASA classification and were scheduled for different surgical interventions were included in the study. The ages of the patients varied between 30-69 years. They were randomly divided into three groups and premedicated with IM 5 mg dehydrobenzperidole, 0.5 mg atropine. Anaesthesia was induced via infusion of IV 5mg/kg thiopentone and 1.5 mg/kg succinylcholine and it was maintained by infusing propofol+fentanyl in group I patients and administering isoflurane in group II, enflurane in group III in equivalent concentrations. Results: When the heart rate and blood pressure values measured before and one minute after extubation were compared with preinduction values, a significant decrease in heart rate was observed in group I, in contrast to an increase in other groups. While there was a significant increase in blood pressure in group II, smaller increments were detected in other groups. All of the groups exhibited a decrease in blood pressure after extubation with respect to preextubation values and these decreases were more prominent in group I. Conclusion: Our findings demonstrate that administration of propofol+fentanyl for the maintenance of anaesthesia in hypertensive patients results in more stable hemodynamic responses during extubation in comparison with the inhalation anesthetics.
Hipertansif hastalarda ekstubasyon ile olusan hemodinamik degisiklikler
Keywords: Anesthesia; Complications; Intratracheal intubation